Respiratory failure, clinical course and community management of COVID‐19 patients in a large Australian cohort. Issue 3 (25th February 2021) - Louie, Teresa; Kwan, Ben; Susanto, Clarissa; Ng, Andrew
Abstract: Background: Coronavirus disease 2019 (COVID‐19) has wreaked health and economic damage globally. A thorough understanding of the characteristics of COVID‐19 patients in Australia plus the strategies that successfully 'flatten the curve' are vitally important to contain this pandemic. Aim: To describe the clinical characteristics and outcomes of COVID‐19 patients in the Sutherland Shire, and the management model adopted to manage these patients. Methods: A retrospective case series of COVID‐19 patients monitored in the Sutherland Shire between 19 March and 15 May 2020 was performed. Demographic, clinical and outcome data of COVID‐19 inpatients at the Sutherland Hospital and demographic data of COVID‐19 patients in the Sutherland Shire community were obtained. The Sutherland Hospital COVID‐19 Management Model involved close collaboration among the Sutherland Fever Clinic, Sutherland COVID‐19 community telemonitoring team (CTAC) and Sutherland COVID‐19 inpatient team. Results: Ninety‐nine COVID‐19 cases (median age, 49 years, 50 (51%) male) were monitored in Sutherland Shire, with 19 cases (median age, 54 years, 10 (53%) male) requiring inpatient management. Common comorbidities included obesity, asthma, hypertension and Type 2 diabetes mellitus. Six (32%) patients required supplemental oxygen and three (16%) patients required intensive care admission. There was one mortality. The CTAC team identified five (5%) patients requiring admission, and three (3%) patients requiring re‐admission. The majority of COVID‐19 source was from overseas travel (67%), with nine (9%) cases having unknown source. Conclusion: A comprehensive COVID‐19 management model is needed to successfully manage COVID‐19 patients in both outpatient and inpatient settings in order to 'squash the curve'.